Somatic CRISPR/Cas9-mediated tumour suppressor disruption enables versatile brain tumour modelling - Zuckermann, Marc; Hovestadt, Volker; Knobbe-Thomsen, Christiane B.; Zapatka, Marc; Northcott, Paul A.; Schramm, Kathrin; Belic, Jelena; Jones, David T. W.; Tschida, Barbara; Moriarity, Branden; Largaespada, David; Roussel, Martine F.; et al. (Nature Communications, 2015)
In vivo functional investigation of oncogenes using somatic gene transfer has been successfully exploited to validate their role in tumorigenesis. For tumour suppressor genes this has proven more challenging due to technical aspects. To provide a flexible and effective method for investigating somatic loss-of-function alterations and their influence on tumorigenesis, we have established CRISPR/Cas9-mediated somatic gene disruption, allowing for in vivo targeting of TSGs. Here we demonstrate the utility of this approach by deleting single (Ptch1) or multiple genes (Trp53, Pten, Nf1) in the mouse brain, resulting in the development of medulloblastoma and glioblastoma, respectively. Using whole-genome sequencing (WGS) we characterized the medulloblastoma-driving Ptch1 deletions in detail and show that no off-targets were detected in these tumours. This method provides a fast and convenient system for validating the emerging wealth of novel candidate tumour suppressor genes and the generation of faithful animal models of human cancer.
Gesehen am 09.10.2020